Demographic and metabolic characteristics of individuals with progressive glucose tolerance - Mendes, A. L. [UNESP]; Santos, M. L. [UNESP]; Padovani, C. R. [UNESP]; Pimenta, W. P. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2009)
We evaluated changes in glucose tolerance of 17 progressors and 62 non-progressors for 9 years to improve our understanding of the pathogenesis of type 2 diabetes mellitus. Changes in anthropometric measurements and responses to an oral glucose tolerance test (OGTT) were analyzed. We identified 14 pairs of individuals, one from each group, who were initially normal glucose tolerant and were matched for gender, age, weight, and girth. We compared initial plasma glucose and insulin curves (from OGTT), insulin secretion (first and second phases) and insulin sensitivity indices (from hyperglycemic clamp assay) for both groups. In the normal glucose tolerant phase, progressors presented: 1) a higher OGTT blood glucose response with hyperglycemia in the second hour and a similar insulin response vs non-progressors; 2) a reduced first-phase insulin secretion (2.0 ± 0.3 vs 2.3 ± 0.3 pmol/L; P < 0.02) with a similar insulin sensitivity index and a lower disposition index (3.9 ± 0.2 vs 4.1 ± 0.2 µmol·kg-1·min-1 ; P < 0.05) vs non-progressors. After 9 years, both groups presented similar increases in weight and fasting blood glucose levels and progressors had an increased glycemic response at 120 min (P < 0.05) and reduced early insulin response to OGTT (progressors, 1st: 2.10 ± 0.34 vs 2nd: 1.87 ± 0.25 pmol/mmol; non-progressors, 1st: 2.15 ± 0.28 vs 2nd: 2.03 ± 0.39 pmol/mmol; P < 0.05). Theses data suggest that β-cell dysfunction might be a risk factor for type 2 diabetes mellitus.
Keywords: Impaired glucose tolerance; Impaired insulin secretion; Normal glucose tolerance; Hyperglycemic clamp; Oral glucose tolerance test